Exploring the Application of Jung's Psychological Types in Psychodrama: A Case Study on Attempting to Mitigate Intergenerational Trauma Between Mothers and Daughters - Chen, Jiayuan; Jian, Ruixi; Qiu, Hanfei (Transactions on Social Science, Education and Humanities Research, 2024)
Nowadays, many people learn their personality types through the popular MBTI personality test which is based on Jung’s theory about types. Many lonely, sensitive, and trust-seeking young people are inspired by Beebe Mode to explore the identities of different personality types for spiritual development in contributing to their mental conditions and potential abilities. Noticing that this process of self-awareness and self-identification of recognizing, exploring, and healing is similar to the acting methods used by actors, this research realized that combining Jung’s psychological types with acting approaches is a good opportunity to respond to the psychological problems of young people. Psychodrama is a psychotherapeutic approach that focuses on dealing with an individual's present-day issues, designed to bring the person’s consciousness back into their mental world, which provides a basic form to examine theories in this passage. In a scenario of the performance, the attendee plays different roles to vent inner suppressing emotions and experience the thoughts and feelings of different characters, which leads to new insights and realizations to establish new appropriate behaviors. Through literature analysis, questionnaires, and interviews, the information gathered in this paper shows that women in China are affected by intergenerational trauma in greater numbers in the current social context. Analyzing the causes of its formation, this paper will use the example of a psychodrama workshop focusing on intergenerational trauma, to prove a connection between the Beebe Mode and performance methods and their usefulness in psychodrama in responding to participants' questions about intergenerational trauma.